Semi-batch industrial process of nitriles production: Dynamic simulation and validation. (2nd November 2018) - Brito, K.D.; Vasconcelos, S.F.; Neto, G.F. Farias; Damasceno, A.S.; Figueirêdo, M.F.; Ramos, W.B.; Brito, R.P.
Highlights: Semi-batch production of nitrile from fatty acid and ammonia was computer simulated using Aspen Plus and Aspen Plus Dynamics. Comparison and validation with industrial data was done. Opportunities for improving the process were evaluated and the main result is a reduction in batch cycle time. Abstract: A semi-batch reactor is used to produce nitriles by reacting fatty acids and ammonia. Despite it is an old chemical process and many patents are available in the literature, its mathematical model was not developed until now. This process comprises a semi-batch reactor with recycle, which makes the numerical solution a challenge to face. In this paper, the entire process has been computer simulated for the very first time. Aspen Plus software was used to find the initial condition for the set of differential algebraic equations, which will be solved by Aspen Plus Dynamics, the key tool to ensure that the entire batch cycle could be properly programmed. Besides that, PI controllers were implemented to guarantee normal and safety operation of the process evaluated, in other words, controllers performed well in tracking pressure and composition profiles, target conversion for the desired product and level behavior. The simulated results were validated with industrial data and opportunities for improving the process were evaluated. The main result was a reduction in batch cycle time for around 40 min.